Cycloaddition reactions of conjugated azoalkenes - Lemos, A. (2010)
An overview of the use of 2H-azirines, conjugated nitrosoalkenes and conjugated azoalkenes bearing phosphorus substituents in addition and cycloaddition reactions is presented, focused on strategies for the synthesis of aminophosphonate and aminophosphine oxide derivatives.